2018
DOI: 10.1080/14017431.2018.1499955
|View full text |Cite
|
Sign up to set email alerts
|

Association between the promoter methylation of the TBX20 gene and tetralogy of fallot

Abstract: The downregulated methylation level at TBX20 promoter may be responsible for the elevated mRNA expression levels in patients with TOF. The abnormal methylation status of the TBX20 promoter may contribute to the pathogenesis of TOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Thus, during this period, the fetal troponin I1 isoform (Tnni1) is repressed by methylation, and, on the contrary, the postnatal Troponin I3 isoform (Tnni3) is activated through demethylation [ 127 , 129 ]. In the myocardium of patients with TF, high levels of methylation of the NKX2-5 and HAND1 promoters [ 130 ] and low levels of methylation of the TBX20 promoter are found in comparison with the control group, which is regarded as one of the factors in the pathogenesis of this CHD [ 130 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during this period, the fetal troponin I1 isoform (Tnni1) is repressed by methylation, and, on the contrary, the postnatal Troponin I3 isoform (Tnni3) is activated through demethylation [ 127 , 129 ]. In the myocardium of patients with TF, high levels of methylation of the NKX2-5 and HAND1 promoters [ 130 ] and low levels of methylation of the TBX20 promoter are found in comparison with the control group, which is regarded as one of the factors in the pathogenesis of this CHD [ 130 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genes that belong to the Tbx1 ( TBX1 , TBX18 , and TBX20 ) and Tbx2 ( TBX2 , TBX5 ) subfamilies have been reported as transcriptional activators and gene repressors involved in the formation of chamber myocardium. These genes have also been associated with the development of CHDs, including atrial septal defect (ASD), ventricular septal defect (VSD), mitral valve disease (MVD) and tetralogy of Fallot (TOF), among others [ 5 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These epigenetic modifications play a key role in the pathophysiology of CHDs [ 14 , 15 , 16 , 17 ]. Furthermore, some studies have shown that an imbalance in the status of DNA methylation could change the expression of genes that participate in cardiogenesis [ 8 , 10 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal gene expression during cardiac development leading to CHD may due to changes in the epigenetic landscape surrounding the genes’ regulatory regions, 2 and more complex causes of TOF may therefore be associated with epigenetic variation. A few studies have investigated the role of epigenetic modifications in TOF 1,13‐16 . We previously found that methylation abnormalities in multiple genes were involved in the pathogenesis of TOF 9,17‐19 and detected abnormal expression of some microRNAs (miRNAs) and significant changes in histone modification in injured heart tissues from TOF patients 20‐22 .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the role of epigenetic modifications in TOF. 1,[13][14][15][16] We previously found that methylation abnormalities in multiple genes were involved in the pathogenesis of TOF 9,[17][18][19] and detected abnormal expression of some microRNAs (miRNAs) and significant changes in histone modification in injured heart tissues from TOF patients. [20][21][22] As the largest class and most important component of non-coding RNAs, long non-coding RNAs (lncRNAs) of over 200 nucleotides are numerous in eukaryotes and function as transcriptional regulators in many cell processes and diseases.…”
Section: Introductionmentioning
confidence: 99%